Acute hydrodynamic damage induced by SPLITT fractionation and centrifugation in red blood cells (2016)
Though blood bank processing traditionally employs centrifugation, new separation techniques may be appealing for large scale processes. Split-flow fractionation (SPLITT) is a family of techniques that separates in absence of labelling and uses very low flow rates and force fields, and is therefore expected to minimize cell damage. However, the hydrodynamic stress and possible consequent damaging effects of SPLITT fractionation have not been yet examined. The aim of this study was to investigate the hydrodynamic damage of SPLITT fractionation to human red blood cells, and to compare these effects with those induced by centrifugation. Peripheral whole blood samples were collected from healthy volunteers. Samples were diluted in a buffered saline solution, and were exposed to SPLITT fractionation (flow rates 1-10 ml/min) or centrifugation (100-1500 g) for 10 min. Cell viability, shape, diameter, mean corpuscular hemoglobin, and membrane potential were measured. Under the operating conditions employed, both SPLITT and centrifugation maintained cell viability above 98%, but resulted in significant sublethal damage, including echinocyte formation, decreased cell diameter, decreased mean corpuscular hemoglobin, and membrane hyperpolarization which was inhibited by EGTA. Wall shear stress and maximum energy dissipation rate showed significant correlation with lethal and sublethal damage. Our data do not support the assumption that SPLITT fractionation induces very low shear stress and is innocuous to cell function. Some changes in SPLITT channel design are suggested to minimize cell damage. Measurement of membrane potential and cell diameter could provide a new, reliable and convenient basis for evaluation of hydrodynamic effects on different cell models, allowing identification of optimal operating conditions on different scales. © 2016 Elsevier B.V.